2004
DOI: 10.1096/fj.04-2095fje
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in atherosclerosis‐prone mouse is due to low antioxidant capacity of mitochondria

Abstract: Atherosclerotic disease remains a leading cause of death in westernized societies, and reactive oxygen species (ROS) play a pivotal role in atherogenesis. Mitochondria are the main intracellular sites of ROS generation and are also targets for oxidative damage. Here, we show that mitochondria from atherosclerosis-prone, hypercholesterolemic low-density lipoprotein (LDL) receptor knockout mice have oxidative phosphorylation efficiency similar to that from control mice but have a higher net production of ROS and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
20

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 25 publications
4
80
0
20
Order By: Relevance
“…In support of a role for mitochondrial injury in atherosclerotic lesion formation, Ballinger et al 31 reported that atherosclerosis-prone apoE-null mice deficient in mitochondrial manganese superoxide dismutase exhibit increased mitochondrial damage and accelerated atherosclerosis. Our data are also in good agreement with recent findings by Oliveira et al, 32 which suggest that a low antioxidant status of mitochondria from LDL-R Ϫ/Ϫ mice may contribute to atherogenesis. The authors provide evidence that a shift in the GSH/GSSG ratios to a more oxidized state contributes to the lower antioxidant status of mitochondria isolated from atherosclerosis-prone LDL-R Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 93%
“…In support of a role for mitochondrial injury in atherosclerotic lesion formation, Ballinger et al 31 reported that atherosclerosis-prone apoE-null mice deficient in mitochondrial manganese superoxide dismutase exhibit increased mitochondrial damage and accelerated atherosclerosis. Our data are also in good agreement with recent findings by Oliveira et al, 32 which suggest that a low antioxidant status of mitochondria from LDL-R Ϫ/Ϫ mice may contribute to atherogenesis. The authors provide evidence that a shift in the GSH/GSSG ratios to a more oxidized state contributes to the lower antioxidant status of mitochondria isolated from atherosclerosis-prone LDL-R Ϫ/Ϫ mice.…”
Section: Discussionsupporting
confidence: 93%
“…VCAM-1 is expressed in the endothelial cells of ApoE-deficient mice fed a Western diet (Nakashima et al, 1998); however, the cellular mechanisms of FFAinduced VCAM-1 expression in HUVECs and the aortic root are not fully understood. Oxidative stress is an important mediator of VCAM or ICAM expression and atherosclerosis progression (Maloney et al, 2009;Oliveira et al, 2005). Saturated fatty acid stimulates IL-6 and ICAM expression through the production of reactive oxygen species by mitochondria and NADPH oxidase in human microvascular endothelial cells (Maloney et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Saturated fatty acid stimulates IL-6 and ICAM expression through the production of reactive oxygen species by mitochondria and NADPH oxidase in human microvascular endothelial cells (Maloney et al, 2009). It is interesting that saturated fatty acids activate NF-kB translocation from the cytoplasm to the nucleus, generating reactive oxygen species (Cacicedo et al, 2004;Oliveira et al, 2005). Ceramide, which is produced from palmitate and serine through de novo synthesis of ceramide and DAG-activated PKC, which is a byproduct of palmitate, is a possible mediator of the induction of adhesion molecule expression.…”
Section: Discussionmentioning
confidence: 99%
“…iNOS appears to play an integral role in the development of atherosclerotic lesions and is responsible for the NO, O 2 − and OONO − generated by infiltrated immune cells (Ponnuswamy et al, 2009). Mitochondrial-derived oxidative stress has also been observed in several tissues from hypercholesterolemic, atherosclerosis prone animal models and in human aortic tissue (Ballinger et al, 2002;Oliveira et al, 2005). Besides the changes observed with respect to ROS generation, vascular antioxidant defenses are also altered during atherosclerosis.…”
Section: Cardiovascular Diseasementioning
confidence: 97%